Cancers of unknown primary diagnosed during hospitalization: a population-based study. Issue 1 (December 2017) - Jones, William; Allardice, Gwen; Scott, Iona; Oien, Karin; Brewster, David; Morrison, David
Abstract Background Cancers of Unknown Primary (CUP) are the 3-4th most common causes of cancer death and recent clinical guidelines recommend that patients should be directed to a team dedicated to their care. Our aim was to inform the care of patients diagnosed with CUP during hospital admission. Methods Descriptive study using hospital admissions (Scottish Morbidity Record 01) linked to cancer registrations (ICD-10 C77-80) and death records from 1998 to 2011 in West of Scotland, UK (population 2.4 m). Cox proportional hazards models were used to assess effects of baseline variables on survival. Results Seven thousand five hundred ninety nine patients were diagnosed with CUP over the study period, 54.4% female, 67.4% aged ≥ 70 years, 36.7% from the most deprived socio-economic quintile. 71% of all diagnoses were made during a hospital admission, among which 88.6% were emergency presentations and the majority (56.3%) were admitted to general medicine. Median length of stay was 15 days and median survival after admission 33 days. Non-specific morphology, emergency admission, age over 60 years, male sex and admission to geriatric medicine were all associated with poorer survival in adjusted analysis. Conclusions Patients with a diagnosis of CUP are usually diagnosed during unplanned hospital admissions and have very poor survival. To ensure that patients with CUP are quickly identified and directed to optimal care, increased surveillance and rapid referral pathways will be required.